Nefropatia associata al SARS-CoV-2: cosa sappiamo finora - Aris Tsalouchos; Maurizio Salvadori (AboutScience Srl, 2020)
Acute kidney injury (AKI) is a frequent complication of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) attributable to i) hypotension and decreased kidney perfusion secondary to hemodynamic or hemostatic factors, ii) drug-induced nephrotoxicity, iii) cytokine storm syndrome related to sepsis. However: i) early new-onset proteinuria and hematuria in many patients, ii) the identification of SARS-CoV-2 viral load in precisely defined kidney compartments, iii) ultrastructural evidence of direct viral infection of the kidneys, and most importantly, iv) morphological alterations associated to cytopathic action induced by the virus support the existence of SARS-CoV-2 associated nephropathy. In addition, collapsing glomerulopathy reported in African American patients with underlying APOL1 kidney risk alleles and SARS-CoV-2 infection is the evidence of a distinct form of SARS-CoV-2 associated nephropathy, the APOL1-SARS-CoV2-associated nephropathy.